The Effect of Generating Interactions among Schemata, Texts, and Beliefs about Language Learning on Reading Comprehension - Adnyani, Luh Dyah Surya (Lingua Scientia, 2011)
This study concerned with experimental research which investigated whether or not there was any effect of Generating Interaction between Schemata and Text (GIST) and beliefs about language learning on reading comprehension. This study was carried out in Universitas Pendidikan Ganesha 2nd semester students at English Education Department. ANOVA test indicated that the students who were taught using GIST outperformed the students who were taught using conventional reading technique, and there was interaction between kinds of strategy and students’ beliefs about language learning. In terms of beliefs about language learning, the result of Tuckey test showed that for the students who hold positive beliefs, GIST gave better contribution to reading comprehension than the conventional reading technique. While for those who hold negative beliefs, there was no significant difference in reading comprehension between the students who were taught using GIST and conventional reading technique.